SIGNIFICANCE OF TEACHER COMPETENCE TOWARDS THE IMPLEMENTATION OF AUTHENTIC ASSESSMENT AT MTS AL-KHAIRIYAH BADAMUSALAM SERANG CITY - Safuroh Safuroh; Wasehudin Wasehudin; Fandy Adpen Lazzvietamsi; Ade Faqih Kurniawan; Nanang Faturachman; Nurul Indana (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
This paper aims to analyze teachers' competencies in conducting authentic assessments in the affective (attitude), cognitive (knowledge), and psychomotor (skills) domains. This aligns with Law Number 14 of 2005, Article 10, Paragraph 1 concerning Teachers and Lecturers, which stipulates that teachers must possess various competencies to carry out their teaching and educational duties professionally, ensuring that academic goals are effectively achieved. The method used in this study is a quantitative field survey analyzed using statistical methods. The population and sample in this study consist of 17 educators, specifically all educators at MTs Al-Khairiyah Badamusalam, Serang City, using a saturated sampling technique. The results show that the competence of MTs Al-Khairiyah Badamusalam teachers in conducting authentic assessments in the affective domain scored 70.58%, within the range of 61% to 80% (good). The teachers' ability to conduct authentic assessments in the cognitive domain reached 94.11%, within the range of 81% to 100% (very good). Their ability to conduct authentic assessments in the psychomotor domain achieved a score of 83.19%, within the range of 81% to 100% (very good). Through the implementation of authentic assessments in the learning process, it is hoped that the educational objectives at the educational unit level can be realized.